An Integration Model of Planned Maintenance and Spare Parts Inventory for Periodic Order Policy - Norhafiza MohdNoor; Nerda Zura Zaibidi; Zurina Hanafi (International Journal of Supply Chain Management, 2018)
The availability of spare parts is very crucial to enable the maintenance tasks to be performed when required. Although failures occur at random, a certain amount of spare parts should be available to minimize the downtime required for repairing or replacing the failed items. Particularly when preventive maintenance is involved, spare parts may be needed to replace the defective but still working plant items. Thus, spare parts and planned maintenance are significantly related and should be studied together. By implementing the delay time concept, this study focus on periodic order policy and simultaneously optimize three decisions problems, namely inspection interval, order interval and maximum stock level. A numerical example is presented to illustrate the ability of the model.